Analysis of Process Skills Profile of Students of Haqqul Mubin Integrated High School as a Driving School - Zahara, Leni; Ruslan, Ruslan; Yunus, Muhammad (Riwayat: Educational Journal of History and Humanities, 2025)
Analysis of Process Skills Profile of Students of Haqqul Mubin Integrated High School as a Driving School. Education in Indonesia faces challenges in improving the quality of graduates to compete in the industrial era 5.0. Reform through the Driving School Program aims to develop students' skills, including observation, classification, and communication. Despite the progress, students still have difficulty in applying new techniques. Innovative approaches are needed to ensure quality education and prepare students for global challenges. This research aims to identify and evaluate the skills possessed by students of Haqqul Mubin Integrated High School in the learning process. This research focuses on observation, classification, and prediction skills, as well as the development of these skills after school transformation. The method used was a qualitative approach with a descriptive type of research, involving interviews with two informants: SMAT homeroom teacher Haqqul Mubin and students. The results of the study show that, (1) The types of process skills possessed by students at Haqqul Mubin Integrated High School include observation, classification, prediction, and communication skills. (2) The development of process skills at SMAT Haqqul Mubin after transforming into a Driving School, the development of these skills is still limited. Students often still rely on old methods in observing and grouping data. For this reason, a more innovative and interactive learning approach is needed so that students can develop process skills thoroughly and be ready to face various challenges in the future.